Report on the Results of the Use of Soccer Training Activities, for Students Matthayom Suksa 4, Sisaket Sports School - Naka, Phuthiphong (Academic MCU Buriram Journal, 2021)
The purposes of this study were: 1) to find the efficacy of the activity package for football training for grade 10 students according to the criteria of 80/80, 2) to find the effectiveness index of grade 10 students using the activity package for football training, 3) to compare the learning achievement of grade 10 students before and after using the activity package for football training, and 4) to study the students’ satisfaction towards the activity package for football training. The samples in this study were 24 grade 10 students in the second semester of academic year 2018 of Sisaket Sports School. The research instruments included 4 books of the activity package for football training for grade 10 students, 100 sheets of teaching plans, an achievement test which is a multiple choices test consisting of 40 items (The difficulty index is between 0.33-0.80, the discriminant index is between 0.36-0.80, and the reliability is 0.85.), and student satisfaction questionnaire including 20 items (The discriminant index is between 0.23-0.87 and the reliability is 0.89). Statistics used for data analysis included mean, percentage, and t-test. The research result finds that: The efficacy of the activity package for football training for the grade 10 students was equal to 82.08/93.54 The effectiveness index of using the activity package for football training of the grade 10 students was 0.8749 showing that the students' development increased to 87.49 %. The learning achievement of the grade 10 students after using the activity package for football training was significantly higher than before using the activity package at the level of 0.01. 4. The students’ satisfaction towards the activity package for football training was at a high level (mean=4.13).